Development of an Online Active Learning Model Using the Theory of Multiple Intelligence to Encourage Thai Undergraduate Student Analytical Thinking Skills - Rodrangsee, Bovornwich; Tuntiwongwanich, Somkiat; Pimdee, Paitoon; Moto, Sangutai (My University, 2022)
This research aim was to create an online active learning (OAL) model using Multiple Intelligence Theory (MIT) to promote Thai undergraduate analytical thinking skills (ATS). Eight experts assisted with their expertise in the model’s development and five for the model’s final assessment. The research tools used consisted of an interview form and a model assessment form. The results showed that the PPICE learning model consisted of nine elements and five steps. The five steps were preparation and problem determination (Step 1), problem analysis (Step 2), study and collect relevant information to practice thinking (Step 3), conclusion and presentations (Step 4), lesson summary and evaluation (Step 5). The expert's assessment of the PPICE Model revealed that overall the model was at its 'best' level (mean = 4.63, SD = .048). Moreover, the experts judged the model's nine components as the 'best' (mean = 4.74, SD = 0.38), with measurement and evaluation second (mean = 4.70, SD = 0.45), and teaching and learning activity processes third (mean = 4.66, SD = 0.48).
Keywords: active teaching; analytical thinking; online learning; Thailand